Recurrence Patterns After Hepatectomy With Very Narrow Resection Margins for Hepatocellular Carcinoma - Cheng, Chih-Hsien; Lai, Yin; Hung, Hao-Chien; Lee, Jin-Chiao; Wang, Yu-Chao; Wu, Tsung-Han; Lee, Chen-Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Chan, Kun-Ming; Lee, Wei-Chen (Frontiers in Surgery, 2022)
Background: The extent of hepatic resection In HCC depends on the remnant liver reserve or the proximity of the tumor to major vascular structures. However, a wide surgical margin is not always be possible and thus it is necessary to evaluate the effects of very close resection margins on postoperative recurrence. Methods: Consecutive LR for HCC between 2003 and 2009 were studied. Patients were divided into groups with very narrow (≤1mm) or wider (>1mm) resection margins. Propensity score matching (PSM) was used to balance demographic, surgical, and pathological factors. Results: Nine hundred eighty-three patients with more than one year post-op follow-up were included in the study. After PSM, 173 patients were analyzed in each group. The 5-year tumor recurrence and survival rates were comparable. Most recurrences were multiple intrahepatic. The section margin recurrences were similar in both groups. By multivariate analysis, tumor size >5cm was associated with a very narrow resection margin, whereas low platelet count and tumor macrovascular invasion were significant factors related to tumor recurrence. Conclusions: Patients with very narrow surgical margins showed outcomes comparable to those with wider surgical margins. Most recurrences were multiple intrahepatic recurrences and associated with the degree of portal hypertension and adverse tumor biology. Although wide surgical margins should be aimed whenever possible, a narrow tumor-free margin resection still represents an effective therapeutic strategy.